Darrieus vertical axis wind turbines: methodology to study the self-start capabilities considering symmetric and asymmetric airfoils - Batista, Nelson (2018)
The rapid growth of wind power generation and the need for a smarter grid with decentralized energy generation has increased the interest in vertical axis wind turbines (VAWT), especially for the urban areas. For the urban areas the VAWT offer several advantages over the horizontal ones, so their acceptance is rising. The lift-type VAWT (Darrieus wind turbines) have a natural inability to self-start without the help of extra components. The existing methodologies are usually used to optimize the wind turbine performance, but not its ability to self-start. Indeed, studying the aerodynamic behavior of blade profiles is a very complex and time-consuming task, since blades move around the rotor axis in a three-dimensional aerodynamic environment. Hence, a new methodology is presented in this paper to study the self-start ability of VAWT, which offers a substantial time reduction in the first steps of new blade profiles development. Both symmetrical and asymmetrical airfoils are targeted in our study, presenting comprehensive results to validate our methodology.